2017
DOI: 10.3348/kjr.2017.18.1.217
|View full text |Cite
|
Sign up to set email alerts
|

Core Needle Biopsy of the Thyroid: 2016 Consensus Statement and Recommendations from Korean Society of Thyroid Radiology

Abstract: Core needle biopsy (CNB) has been suggested as a complementary diagnostic method to fine-needle aspiration in patients with thyroid nodules. Many recent CNB studies have suggested a more advanced role for CNB, but there are still no guidelines on its use. Therefore, the Task Force Committee of the Korean Society of Thyroid Radiology has developed the present consensus statement and recommendations for the role of CNB in the diagnosis of thyroid nodules. These recommendations are based on evidence from the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
163
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 138 publications
(182 citation statements)
references
References 121 publications
(316 reference statements)
2
163
0
7
Order By: Relevance
“…The FNA and CNB procedures were performed by radiologists under the supervision of 4 clinically experienced thyroid radiologists (J.H.B., J.H.L., J.H.S., and Y.J.C. 19 The operator performed FNA or CNB in accordance with the clinician's preferences.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The FNA and CNB procedures were performed by radiologists under the supervision of 4 clinically experienced thyroid radiologists (J.H.B., J.H.L., J.H.S., and Y.J.C. 19 The operator performed FNA or CNB in accordance with the clinician's preferences.…”
Section: Study Populationmentioning
confidence: 99%
“…Additional CNB procedures were performed when the lesion was considered inaccurately targeted (as was sometimes the case for small nodules) or when an insufficient specimen was suspected on visual inspection. 19…”
Section: Ultrasound-guided Fine-needle Aspiration and Core-needle Bmentioning
confidence: 99%
“…So far, the decision for surgery or clinical follow-up would be dependent on the CNB findings [88, 89]. Some of the controversial studies have reported that CNB is more useful for the patients’ management than repeating FNA.…”
Section: Role Of Core-needle Biopsy In Aus/flusmentioning
confidence: 99%
“…CNB has been suggested as an alternative to FNA in patients with previous nondiagnostic results [12] or atypia of undetermined significance [13]. It is also useful for the differentiation of rapidly growing thyroid tumors (lymphoma vs. anaplastic thyroid carcinoma), the differentiation of follicular lesions (follicular neoplasm vs. nodular hyperplasia), medullary thyroid carcinoma, calcified thyroid nodules, and degenerating thyroid nodules [6,14,15]. Several studies have suggested the value of CNB as a first-line diagnostic tool for the thyroid [16].…”
mentioning
confidence: 99%
“…As the current evidence for the efficacy and safety of thyroid CNB has grown, the KSThR organized a task force team and released the 2016 Thyroid CNB Guidelines [15]. These guidelines include 11 recommendations regarding indications, the device, the procedure, clinical outcomes, and complications.…”
mentioning
confidence: 99%